2019
DOI: 10.1186/s12871-019-0792-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Supreme laryngeal mask airway versus endotracheal intubation for airway management during general anesthesia for cesarean section: a randomized controlled trial

Abstract: Background The obstetric airway is a significant cause of maternal morbidity and mortality. Endotracheal intubation is considered the standard of care but the laryngeal mask airway (LMA) has gained acceptance as a rescue airway and has been incorporated into the obstetric airway management guidelines. In this randomized controlled equivalence trial, we compared the Supreme LMA (SLMA) with endotracheal intubation (ETT) in managing the obstetric airway during cesarean section. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 24 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…It demonstrated that ETT insertion is more irritating than LMA insertion and cause hemodynamic instability. This result is consistent with previous researches demonstrated that the insertion and removal of the LMA was less invasive and induces fewer stress responses than with ETT [18][19][20] . Thus, we suggested that second-generation LMA will be more suitable for patients requiring hemodynamic stability.…”
Section: Discussionsupporting
confidence: 93%
“…It demonstrated that ETT insertion is more irritating than LMA insertion and cause hemodynamic instability. This result is consistent with previous researches demonstrated that the insertion and removal of the LMA was less invasive and induces fewer stress responses than with ETT [18][19][20] . Thus, we suggested that second-generation LMA will be more suitable for patients requiring hemodynamic stability.…”
Section: Discussionsupporting
confidence: 93%
“…Obstetric airway management offers its own unique challenges, with failure reported to carry an incidence of 0.4% globally. 7 Moreover, preterm delivery may lead to significant complications such as neonatal ARDS, visual and hearing problems, poorer neurodevelopmental outcomes and learning difficulties in childhood. 8 In the context of our case, the team-based approach proved to be particularly helpful in aiming to limit adverse outcomes to our patient and the fetus should respiratory deterioration have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SGA in emergency situations such as rescue airway device is easily justifiable as the risks of aspiration outweigh the potential of hypoxaemia and death. However, since 2001, the use of SGA as primary airway device during GA for CD has been demonstrated in several studies and been reviewed on several occasions [8][9][10][11][12][13][14][15][16][17]19,43 && ,44,45 && ,46]. To date, there are at least twelve peer reviewed studies describing the use of SGA as primary airway device (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Supraglottic Airway Devices As Primary Devices In Obstetric ...mentioning
confidence: 99%
“…However, since 2001, the use of SGA as primary airway device during GA for CD has been demonstrated in several studies and been reviewed on several occasions [8][9][10][11][12][13][14][15][16][17]19,43 && ,44,45 && ,46]. To date, there are at least twelve peer reviewed studies describing the use of SGA as primary airway device (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19]. Eight articles describe the use of SGA as a primary airway device during elective CDs under GA [8,9,[11][12][13][14]18,19], three studies report the use of SGA in elective and emergency caesarean deliveries [10,16,17] and one study in emergency cases only [15].…”
Section: Supraglottic Airway Devices As Primary Devices In Obstetric ...mentioning
confidence: 99%
See 1 more Smart Citation